2017
DOI: 10.1186/s13229-017-0140-1
|View full text |Cite|
|
Sign up to set email alerts
|

Neural synchronization deficits linked to cortical hyper-excitability and auditory hypersensitivity in fragile X syndrome

Abstract: BackgroundStudies in the fmr1 KO mouse demonstrate hyper-excitability and increased high-frequency neuronal activity in sensory cortex. These abnormalities may contribute to prominent and distressing sensory hypersensitivities in patients with fragile X syndrome (FXS). The current study investigated functional properties of auditory cortex using a sensory entrainment task in FXS.MethodsEEG recordings were obtained from 17 adolescents and adults with FXS and 17 age- and sex-matched healthy controls. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
173
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(206 citation statements)
references
References 56 publications
20
173
0
Order By: Relevance
“…Increased activation of left hemispheric circuitry, including superior temporal gyrus, was observed in FXS subjects during an auditory temporal discrimination task . FXS subjects also show reduced synchronization of neural responses to time‐varying signals, suggesting impairments in temporal processing . Rojas et al showed that tone‐evoked responses measured using magnetic fields are higher in the auditory cortex of individuals with FXS .…”
Section: Fmrp Loss Alters Auditory Cortical Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Increased activation of left hemispheric circuitry, including superior temporal gyrus, was observed in FXS subjects during an auditory temporal discrimination task . FXS subjects also show reduced synchronization of neural responses to time‐varying signals, suggesting impairments in temporal processing . Rojas et al showed that tone‐evoked responses measured using magnetic fields are higher in the auditory cortex of individuals with FXS .…”
Section: Fmrp Loss Alters Auditory Cortical Activitymentioning
confidence: 99%
“…46 FXS subjects also show reduced synchronization of neural responses to time-varying signals, suggesting impairments in temporal processing. 109 Rojas et al 110 showed that tone-evoked responses measured using magnetic fields are higher in the auditory cortex of individuals with FXS. 110 EEG recordings revealed increased gamma frequency band power in resting state EEG of FXS patients.…”
Section: Auditory Cortical Activit Ymentioning
confidence: 99%
“…Differences in synaptic activity are a defining and unifying characteristic of animal models of autism—virtually, every report of an autism model includes electrophysiological characterization showing altered synaptic transmission. The directionality of change in synaptic activity is also variable between models; for example Ube3a 2xTG mice show reduced cortical excitability [ 32 ] while Fragile X [ 53 , 54 ] mice show increased. Viewed through this activity-dependent lens, the bidirectionality of our data makes more sense.…”
Section: Discussionmentioning
confidence: 99%
“…For example, about one-third of FXS-affected individuals exhibit cortical hyperexcitability. 336 If such hyperexcitability can be modeled in FXS iPSC-differentiated neurons, it will provide an excellent platform for understanding the molecular mechanism of the presence and absence of hyperexcitability and provide an opportunity to prescreen individuals for clinical trials. Therefore, hPSCs are essential for validating the molecular, cellular, and functional FXS deficits that we have known for years on the basis of animal studies.…”
Section: Human Stem Cells For Modeling Neurodevelopmental Disordersmentioning
confidence: 99%
“…For example, recent work has indicated that variability in behavior and cognition in FXS could be linked to variability in electrical activity in the brain of FXSaffected individuals, as measured by EEG. 223,336 One solution is the establishment of high-quality iPSCs from individuals with well-characterized and stratified clinical features. Stratification of affected individuals and cells could enable more effective linkage of disease characteristics with cellular phenotypes and better design of clinical trials.…”
Section: Challenges and Perspectives Clinical Variabilitymentioning
confidence: 99%